Echinodorus australis (alismataceae), a new synonym for helanthium bolivianum - Zanotti, Christian Alejandro (2019)
Echinodorus australis Rataj, a species from southern Brazil and northern Argentina, is here synonymized under Helanthium bolivianum (Rusby) Lehtonen & Myllys.